2016
DOI: 10.1371/journal.pone.0149363
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Seeking Behavior for Suspected Human and Animal Rabies Cases, Gomma District, Southwest Ethiopia

Abstract: BackgroundTimely presentation to appropriate health service provider of sick animals/humans from zoonotic diseases like rabies is important for early case/outbreak detection and management. However, data on community’s health seeking practice for rabies in Ethiopia is limited. Therefore the objective of this study was to determine community’s health seeking behavior on rabies, Southwest Ethiopia.MethodsA cross-sectional survey was conducted from January 16-February 14, 2015 to collect data from 808 respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The mean age of the participants was of 26.45 (SD = 4.76). Direct attitude, subjective norm, and perceived behavioral control had a mean score of 16.78 (SD = 2.87), 15.61(SD = 1.92), and 12.86 (SD = 4.85), respectively. The intention has a mean score of 14.52 (SD = 4.01).…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of the participants was of 26.45 (SD = 4.76). Direct attitude, subjective norm, and perceived behavioral control had a mean score of 16.78 (SD = 2.87), 15.61(SD = 1.92), and 12.86 (SD = 4.85), respectively. The intention has a mean score of 14.52 (SD = 4.01).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, strong believe in traditional medicine for the treatment of rabies has been discovered. This indicates low level of community attitude towards the disease [16, 18, 29, 30]. In Eastern Ethiopia, one study confirmed that majority of the respondents have heard about the disease from their family in both urban and pastoralist households [19] which implied government based awareness creation might not be adequate or practiced.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been conducted in Ethiopia ( 20 22 ) to explore knowledge, attitude, practice and socio-demographic factors influencing rabies control. However, the link between these factors and dog owners' intention to vaccinate against rabies remain unclear.…”
Section: Introductionmentioning
confidence: 99%